Elusive 2H-1, 2-oxasiletes through reactions of an isolable dialkylsilylene with diazocarbonyl compounds1. Issue 36 (28th September 2015) - Dong, Zhaowen; Xiao, Xu-Qiong; Li, Zhifang; Lu, Qiong; Lai, Guoqiao; Kira, Mitsuo
<x xml:space="preserve">Abstract</x> The reactions of isolable dialkysilylene 1 with compounds 5 and 6 gave elusive silacycles, 2H-1, 2-oxasiletes 2 and 3, respectively, with releasing dinitrogen. In contrast, six-membered cyclic diazo compound 8 was obtained in a good yield by the reaction of 1 with less reactive 7.